Challenges in Comparing Interest Rates : A Focus on India's Banking System - Rangotra, Rahul (Indian Journal of Finance, 2026)
Purpose : The article highlighted the challenges faced by the depositors and borrowers in India to compare the interest rates across banks and other institutions. Methodology : Three major Indian banks, State Bank of India (SBI), HDFC Bank, and ICICI Bank, for comparison with United States banks, SBI California and Royal Bank of Canada (RBC), were selected. Only three banks from India were selected because all other banks similarly quoted the interest rates. Findings : It was found that the banks in India quoted the interest rates in nominal terms without taking into account the effect of compounding, processing fees, and other charges, which makes the interest rates difficult to compare. Practical Implications : The paper emphasized that banks should quote the effective interest rates (EIR) instead of nominal interest rates. For the interest of the depositors and borrowers, the RBI should intervene and issue guidelines in this regard. Originality : The paper tried to fill the research gap and suggested that the banks and other institutions involved in lending and borrowing should quote EIR along with nominal interest rates.